2018
DOI: 10.21276/apalm.2358
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Non-Cirrhotic Portal Fibrosis (NCPF) With Special Emphasis on Advanced Fibrosis

Abstract: Background: Non-cirrhotic portal hypertension includes primarily the cases of non-cirrhotic portal fibrosis (NCPF) and extra-hepatic portal vein obstruction, both showing no significant parenchymal disease. NCPF is a disease of uncertain etiology characterized by periportal fibrosis with small and medium sized portal vein branches involvement. Most study done in the past are clinical, hence we decided to analyse its histo-pathological features with clinical correlation. Methods: This is four and half year's re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Previously, a study of NCPH from our group showed the median hepatic venous pressure gradient (HVPG) and liver stiffness (LS, Fibroscan) values were 8 mm of Hg (range: 5-20 mm of Hg) and 9.2 kPa (range: 4.4-26.3 kPa), respectively [7]. This study indirectly indicated that a subset of patients with NCPH can have high HVPG and TE.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previously, a study of NCPH from our group showed the median hepatic venous pressure gradient (HVPG) and liver stiffness (LS, Fibroscan) values were 8 mm of Hg (range: 5-20 mm of Hg) and 9.2 kPa (range: 4.4-26.3 kPa), respectively [7]. This study indirectly indicated that a subset of patients with NCPH can have high HVPG and TE.…”
Section: Discussionsupporting
confidence: 52%
“…The categories of NCPH based on histological characteristics [5][6][7][8] that were used for the categorization into appropriate entities are tabulated in Table 1. Cases were classi ed a priori into six categories: obliterative portal venopathy (OPV), obliterative portal venopathy with brosis (OPV-F), incomplete septal cirrhosis (ISC), nodular regenerative hyperplasia (NRH), megasinusoids with brosis (MSF), [Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation